A case of mistaken identity: Saksenaea vasiformis of the orbit. (2nd November 2021) - Chen, Allison J.; Ediriwickrema, Lilangi S.; Verma, Rohan; Vavinskaya, Vera; Shaftel, Solomon; Deconde, Adam S.; Korn, Bobby S.; Kikkawa, Don O.; Liu, Catherine Y.
ABSTRACT: The authors describe a rare presentation of invasive fungal rhino-orbital cellulitis caused by Saksenaea vasiformis in an immunocompetent child. The patient was initially diagnosed and treated as Mucoraceae, which has a high mortality rate and is primarily seen in immunocompromised patients. Though of the same order, Mucorales, the families Mucoraceae and Saksenaeacae, may be difficult to differentiate on histologic examination and must be distinguished by fungal culture and speciation. Our patient responded well to sino-orbital debridement and systemic treatment with amphotericin and posaconazole.